Intrathoracic Myelomeningocele masquerading as Bronchogenic Cyst: A Case Report (Pulse, 2025)
Neurofibromatosis is an autosomal dominant disorder that affects multiple organs and systems with different complications. Of the 2 types, Neurofibromatosis type 1, also known as von Recklinghausen Syndrome, is more common (96 %) . In this type, rare intrathoracic meningoceles often occur alongside bone dysplasia. This case has been reported as incidental finding of an intrathoracic myelomeningocele in a known patient of neurofibromatosis type 1 which was mistakenly diagnosed as bronchogenic cyst. This error could have put the patient at risk of incorrect treatment, unnecessary invasive procedure, surgery. It reflects the importance of clinical suspicion, the need for advanced imaging techniques and their correct interpretation.Pulse, Volume 16, Issue 2 2024: 39-42